2014
DOI: 10.1016/j.neuron.2014.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Representations Are Reinstated by the Hippocampus during Memory Retrieval

Abstract: The hippocampus is assumed to retrieve memory by reinstating patterns of cortical activity that were observed during learning. To test this idea, we monitored the activity of individual cortical neurons while simultaneously inactivating the hippocampus. Neurons that were active during context fear conditioning were tagged with the long-lasting fluorescent protein H2B-GFP and the light-activated proton pump ArchT. These proteins allowed us to identify encoding neurons several days after learning and silence the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
271
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 339 publications
(309 citation statements)
references
References 31 publications
24
271
1
Order By: Relevance
“…Given the highly parallel nature of neural connectivity and processing, it is possible that although these ensembles may be sufficient for retrieval, they are not necessary as other pathways could compensate. The question of necessity was addressed in two recent studies using a light-gated proton pump from archaebacteria (ArchT) to hyperpolarize and silence cfos tagged neural ensembles in experiments analogous to those described above with ChR2 (Denny et al 2014;Tanaka et al 2014). Both teams of investigators also used context fear conditioning and examined the requirement for ensembles in three different hippocampal regions, the DG, CA3, and CA1.…”
Section: Memory Retrieval In Mice and Menmentioning
confidence: 99%
“…Given the highly parallel nature of neural connectivity and processing, it is possible that although these ensembles may be sufficient for retrieval, they are not necessary as other pathways could compensate. The question of necessity was addressed in two recent studies using a light-gated proton pump from archaebacteria (ArchT) to hyperpolarize and silence cfos tagged neural ensembles in experiments analogous to those described above with ChR2 (Denny et al 2014;Tanaka et al 2014). Both teams of investigators also used context fear conditioning and examined the requirement for ensembles in three different hippocampal regions, the DG, CA3, and CA1.…”
Section: Memory Retrieval In Mice and Menmentioning
confidence: 99%
“…Similar to cocaine CPP, the dHPC, and in particular the CA1 region has a critical role in acquisition and expression of contextual fear memory (Goshen et al, 2011;Tanaka et al, 2014), but whether changes in dHPC brevican levels affect this memory is unknown. One week after the CPP remote test, the same groups underwent contextual FC (Figure 6d).…”
Section: Overexpression Of Brevican In the Dhpcmentioning
confidence: 99%
“…When the mice were returned to the safe cage, they froze in fear, showing that the fearful memory was incorrectly associated with a safe place 6 . Work from other groups has shown that a similar technique can be used to tag and then block a given memory 7,8 .…”
Section: In Search Of the Engrammentioning
confidence: 99%